A Survey on Trend and Classification of Internet of Things Reviews - Azana Hafizah Mohd Aman; Elaheh Yadegaridehkordi; Zainab Senan Attarbashi; Rosilah Hassan; Yong Jin Park (2020)
The Internet of Things (IoT) is shaping the current and next generation of the Internet. The vision of IoT is to embed communication capabilities with a highly distributed, ubiquitous and dense heterogeneous devices network. This vision includes the adaptation of secure mobile networks, anytime, anywhere, by anyone or anything with new intelligent applications and services. Many efforts have been made to review the literature related to the IoT for the benefit of IoT development. However, many issues need to be addressed to overtake the full potential of the IoT. Therefore, this paper aims to classify and standardize IoT research areas by considering review papers that were published between 2010 and 2019. This paper analyzes a total of 95 related reviews, which were manually selected from databases based on 6 chosen areas. This paper presents the trends and classification of IoT reviews based on 6 research areas, namely, application, architecture, communication, challenges, technology, and security. IoT communication research has been dominating the trends with 21% of total reviews and more than 100% research growth in the last 10 years. Hence, this paper can provide useful insights into specific emerging areas of IoT to assist future research.